Survey of zoonotic parasites and bacteria in faeces of Canada geese (Branta canadensis) in North‐Central Oklahoma. Issue 4 (22nd March 2022) - Nagamori, Yoko; Litherland, Marisa A.; Koons, Nicole R.; Linthicum, Anna R.; Ramachandran, Akhilesh
Abstract: Background: As a population of non‐migratory Canada geese ( Branta canadensis ) has been growing in residential and recreational areas, public concerns on potential acquisition of zoonotic pathogens from Canada geese and their faecal deposits have been increasing. Objectives: The main study objective was to evaluate the prevalence of zoonotic microorganisms, Campylobacter spp., Cryptosporidium spp., Giardia spp. and Salmonella spp. and antimicrobial resistant Escherichia coli in faeces of Canada geese residing in North‐Central Oklahoma, United States. Methods: A total of 204 faecal samples were collected from 11 locations in North‐Central Oklahoma, where public recreational areas such as lakes and ponds were located, and Canada geese were commonly inhabited. Faecal samples were examined by a centrifugal flotation to evaluate the prevalence of Cryptosporidium spp. and Giardia spp. infections. A total of 180 faecal samples were grouped into 36 pooled samples and cultured using standard culture methods to detect the prevalence of Campylobacter spp. and Salmonella spp. infections. The antimicrobial resistance profile was determined on 32 E. coli isolates recovered from the 36 sample pools, using the Kirby Bauer Disk Diffusion method. Results: The targeted zoonotic pathogens were not identified by the faecal examinations performed. Of the 32 E. coli isolates, 17 isolates (53.1%) demonstrated resistance to ≥1 antimicrobial agent. Conclusions: Targeted zoonotic pathogens were not detected among the examined resident Canada geese in North‐Central Oklahoma. The findings of multiple‐antimicrobial resistant E. coli infections are potentially a public health concern although the prevalence was low in this study. Further, larger scale surveys are recommended.